A comparison of quality management for bored pile/drilled shaft (BP/DS) foundation construction and the implementation of recent technologies. Issue 2 (2nd July 2016) - Hertlein, B.; Verbeek, G.; Fassett, R.; Arnold, M.
Abstract : Quality Assurance/Quality Control (QA/QC) requirements and the test results generated through the requirements have been the catalysts to the development of many innovations and improved practices used by contractors today to install bored piles/ drilled shafts (BP/DS). While the need for sophisticated QA/QC practice is acknowledged around the world, practices applied for these kinds of deep foundations differ significantly owing to local, state or federal requirements. This paper reviews QC code and standard guidelines frequently implemented in North America and Europe, along with technological developments over the past decade to assure the installation of a high-quality BP/DS. An overview of common non-destructive and destructive test methods is provided and the implementation in both continents evaluated through survey results.